1949
DOI: 10.1152/ajplegacy.1949.158.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Mechanism of Vagal Cardiostimulation

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1953
1953
1971
1971

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…There is some evidence that acetylcholine released by stimulation of cardiac preganglionic vagal fibers may cause excitation of intracardiac adrenergic structures (6,7). If the cardiac augmentation observed in our experiments were the manifestation of such a mechanism, the administration of an anticholinesterase would be expected to potentiate the observed responses.…”
Section: Recordings From the Bilateral Isovolumetric Preparation Withmentioning
confidence: 61%
See 1 more Smart Citation
“…There is some evidence that acetylcholine released by stimulation of cardiac preganglionic vagal fibers may cause excitation of intracardiac adrenergic structures (6,7). If the cardiac augmentation observed in our experiments were the manifestation of such a mechanism, the administration of an anticholinesterase would be expected to potentiate the observed responses.…”
Section: Recordings From the Bilateral Isovolumetric Preparation Withmentioning
confidence: 61%
“…Middleton and his associates have reported augmented contractility in the atropinized, isolated heart during vagal stimulation and during acetylcholine infusions, implicating excitation of intracardiac sympathetic structures by liberated acetylcholine (6,7). Similar observations have been reported by others (8,9), most recently by Hollenberg et al (10).…”
mentioning
confidence: 60%
“…The after-posi tivity sometimes observd immediately after the interruption of vagal stimulation was abolished by the pretreatment of guinea-pig with reserpine but not by DCI in the con centration of 10-'. Middleton et al (23) have reported that the adrenaline-like substance is released in the perfusion fluid of the cat's heart during vagal stimulation. The result that the after-positivity was not affected by DCI may be attributed to the concentra tion of the drug applied in the present experiment, being enough to block the effect of added amines but not enough to antagonize the adrenaline-like substance released by vagal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Middleton, Middleton, and Toha (1949) have shown that vagus stimulation liberates an adrenalinelike substance from the isolated heart after treatment with atropine, so that the acceleration occurs after a physiological stimulus as well as when nicotine or large doses of acetylcholine are applied. Our experiments show that the stimulant action of nicotine and acetylcholine is present after degeneration of the sympathetic fibres, and is therefore probably related to this vagus acceleration.…”
Section: Discussionmentioning
confidence: 99%